Uji Anti Bakteri Ekstrak Daun Sawo Manila (Manilkara zapota) Terhadap Escherichia coli - Nurul Hasanah; Emmy Harso Kardhinata; Jamilah Nasution (Jurnal Ilmiah Biologi UMA (JIBIOMA), 2019)
Manilkara zapota L was included plant which the most popular in South East of Asian. The society also used young fruit, bark, and Sapilla Manila Leaf as tradisional medicine diaerrhea resistant, because substance of tanin was contained in it could hampered and killed the number of bacterias such as Shigella, Salmonella thypii, Escherichia coli. This research purposed for knowing ability of blocked energy from exstract Sapilla Manila Leaf towards Escherichia coli. This research experimentalsm with used qualitatif methode and diffusion methode. Concentration extract of  Sapilla Manila Leaf which was used namely 5%, 10%, 15%, 20% with 5 times,. The result of research showed that extract Sapilla Manila Leaf with each that concentrat have not hampered growth of Escherichia coli. The possibility was caused by several factors such as the concentration level of the extract, the nature of the bacteria used and the tools used in the solvent evaporation process.